PENGARUH SMART LAYANAN AKADEMIK (SALAMI) TERHADAP MUTU LAYANAN PERSURATAN MAHASISWA MPI UIN KHAS JEMBER - Siti Fatimatus Syarifah; Bela Aprilia Putri, Mahda Sakinah, Siti Magfirotul Laily, Rofiq Hidayat (CV. ADIBA AISHA AMIRA, 2024)
Academic services are a very important component of student needs, especially correspondence. The aim of this research is to determine and analyze the influence of smart academic services (SALAMI) on the quality of student correspondence services. This research was aimed at students of Islamic Education Management (MPI), Faculty of Tarbiyah and Teacher Training (FTIK), Kiai Haji Achmad Siddiq State Islamic University Jember. The research method used in this research is a quantitative method with a comparative causal type of research. The total sample is 30 people and the data obtained will then be analyzed using simple regression to see the influence between the smart academic service variable and the quality of correspondence services. The data collection technique uses an online survey technique with the help of SPSS 23. The results of the research show that there is an influence between the smart academic service variable on the quality of student correspondence services at MPI, UIN Khas Jember. The influence that occurs is positive, which means it can help students in dealing with correspondence problems. This is reinforced by the variable's significant value of 0.000 (very significant).